Anomalous Superior Thyroid Artery - Mehta, Vandana; Suri, Rajesh K.; Arora, Jyoti; Rath, Gayatri; Das, Srijit (Kathmandu University Medical Journal, 2012)
The variations in the pattern of distribution of superior thyroid artery assume paramount importance for neck surgeons, in view of its vital topographical relationship to the external laryngeal nerve. In this study, we report an unusual variation in the arterial supply of the thyroid gland, which was detected during a routine dissection of an adult male cadaver. The right superior thyroid artery was absent whereas the left superior thyroid artery took origin from the left common carotid artery and showed a dominant pattern of distribution supplying the superior aspect of both the left and right lobes of the thyroid gland. It exhibited a usual relationship with the left external laryngeal nerve. The inferior thyroid arteries did not show any unusual distribution. Knowledge of such arterial variations related to the thyroid gland is immensely helpful for surgeons in order to put ligature on anomalous artery and to avoid damage to vital structures in this area, such as the external laryngeal nerve. http://dx.doi.org/10.3126/kumj.v8i4.6246 Kathmandu Univ Med J 2010;8(4):429-31